Fatigue as the Dominant Predictor of Impaired Quality of Life Among Post-Tuberculosis Patients in Yogyakarta, Indonesia - Siti Khotimah; Ana Majdawati; Wawan Ramdani (Direktorat Politeknik Kesehatan Makassar, 2025)
Background: Tuberculosis (TB) remains a significant global health problem. Although bacteriological cure can be achieved, many post-tuberculosis patients experience persistent residual symptoms and a decline in quality of life. Objective: This study aimed to identify factors associated with quality of life among post-tuberculosis patients. A cross-sectional study was conducted among 54 post-tuberculosis patients in Yogyakarta, Indonesia. Quality of life was assessed using the St. George's Respiratory Questionnaire (SGRQ). Bivariate and multivariate analyses (linear regression) were performed to identify factors associated with quality of life. Results: The median SGRQ score was 42.8 (IQR: 12.5–68.3). Fatigue was reported in 20.4% of participants. Multivariate analysis showed that fatigue was the dominant independent predictor (B=28.5, β=0.412, p=0.008), explaining 38.0% of the variance in SGRQ scores.. Conclusion: Fatigue is the dominant independent predictor of impaired quality of life in post-tuberculosis patients. Comprehensive care programs that include fatigue assessment and management are needed to improve the quality of life of TB survivors.